Safety of new DAAs for chronic HCV infection in a real life experience: role of a surveillance network based on clinician and hospital pharmacist. Issue 1 (December 2017) - Nappi, A.; Perrella, A.; Bellopede, P.; Lanza, A.; Izzi, A.; Spatarella, M.; Sbreglia, C.
Abstract Background Direct Antiviral Agents (DAAs) for HCV therapy represents a step ahead in the cure of chronic hepatitis C. Notwithstanding the promising results in several clinical trials, few data are available on adverse effects in real life settings. Methods We have evaluated 170 patients with persistent infection and on those eligible to treatment we have followed up them through a network managed by clinician and hospital pharmacist. Results According to our data we have found that 41% (32 out of 78) of enrolled patients experienced adverse reactions, of these 40% were in those under 65 years while 60% was in patients older than 65 years, SVR was achieved in 88% of the patients (including drop-out). We had 4 drop-out treatment due to major adverse reaction (heart and lung related). Conclusion Even if new antiviral drugs seem to be promising, according to SVR, they require careful follow-up, possibly managed by clinician and hospital pharmacist, to avoid unrecognized side effects which may affect adherence and the real impact of these drugs on chronically infected subjects.